2006
DOI: 10.1099/vir.0.82211-0
|View full text |Cite
|
Sign up to set email alerts
|

Dual topology of the processed hepatitis C virus protein NS4B is influenced by the NS5A protein

Abstract: Among the least-known hepatitis C virus proteins is the non-structural protein 4B (NS4B). It localizes to the endoplasmic reticulum (ER) membrane and induces membrane changes, resulting in a membranous web that is reported to be the locale for virus replication. A model was presented previously for the topology of recombinant HCV NS4B of the 1a genotype based on in vitro data. In this model, the N-terminal tail of a considerable fraction of the NS4B molecules was translocated into the ER lumen via a post-trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
68
1
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(76 citation statements)
references
References 49 publications
(67 reference statements)
6
68
1
1
Order By: Relevance
“…NS4B is a hydrophobic 27-kDa protein located in the ER membrane (7), and has four transmembrane domains with the N and C termini located in the cytoplasm. The N-terminal tail of NS4B has been suggested to be posttranslationally translocated to the ER lumen (8). NS4B protein is known to induce intracellular membrane changes that called a "membranous web" (9).…”
Section: Hepatitis C Virus (Hcv)mentioning
confidence: 99%
“…NS4B is a hydrophobic 27-kDa protein located in the ER membrane (7), and has four transmembrane domains with the N and C termini located in the cytoplasm. The N-terminal tail of NS4B has been suggested to be posttranslationally translocated to the ER lumen (8). NS4B protein is known to induce intracellular membrane changes that called a "membranous web" (9).…”
Section: Hepatitis C Virus (Hcv)mentioning
confidence: 99%
“…Instead, HCV-NS5A physically interacts with various cellular proteins, such as p53, IFNinduced, dsRNA-activated protein kinase, or a novel transcription factor SNF2-related CBP activator protein, to elicit modulator roles in cell-cycle regulation, cellular transformation, and antiviral immune responses (5)(6)(7). HCV-NS5A is a membrane-associated protein that uses its N-terminal amphipathic helix domain and is usually found in the HCV RNA replication complex (8,9). HCV-NS5A is indispensable for HCV RNA replication, because HCV genome replicates in the lipid droplet-associated membrane of the endoplasmic reticulum (ER) (10).…”
Section: H Epatitis C Virus (Hcv)mentioning
confidence: 99%
“…As mentioned above the uncleaved NS2-3 precursor protein in association with NS4A are essential for particles formation [101,118]. Several studies on different pestiviruses have revealed that NS4B is an endoplasmic reticulum (ER)-associated integral membrane protein that contains four putative transmembrane domains flanked by cytoplasmic N-and C-terminal regions [119,120,121,122]. Interaction of CSFV NS4B with molecular components of the immune system has also been reported [123].…”
Section: A Few Salient Features Of the Structure Composition And Funmentioning
confidence: 99%